Migrants, Trade and Market Access - Barthélémy Bonadio (Center for Economic Studies and ifo Institute (CESifo), 2023)
Migrants shape market access: first, they reduce international trade frictions and second, they change the geographical location of domestic demand. This paper shows that both effects are quantitatively relevant. It estimates the sensitivity of exports and imports to immigrant population and quantifies these effects in a model of inter- and intra-national trade and migration calibrated to US states and foreign countries. Reducing US migrant population shares back to 1980s levels increases import (export) trade costs by 7% (2.5%) on average and decreases US natives' real wages by more than 2%. States with higher exposure to immigrant consumer demand (both from within the state and from other states) than to migrant labor supply competition suffer more from the removal of migrants. States with higher export and import exposure suffer more from the increased trade costs.
Keywords: F16; F22; 330; migration; market access; trade